Option C:
{x: –1 < x < 7}
Solution:
Given expression is (x – 2 < 5) ∩ (x + 7 > 6).
Let us first solve the inequality.
First inequality:
⇒ x – 2 < 5
Add 2 on both sides of the expression.
⇒ x – 2 + 2 < 5 + 2
⇒ x < 7
Second inequality:
⇒ x + 7 > 6
Subtract 7 on both sides of the expression.
⇒ x + 7 – 7 > 6 – 7
⇒ x + 7 – 7 > 6 – 7
⇒ x > –1
Now to find the intersection of these inequalities.
(x – 2 < 5) ∩ (x + 7 > 6) = (x < 7) ∩ (x > –1)
= (x < 7) ∩ (–1 < x)
= –1 < x < 7
Thus, option C is the correct answer.
(x – 2 < 5) ∩ (x + 7 > 6) = {x: –1 < x < 7}